Domain-wall boundaries through non-diagonal twists in the six-vertex model. (5th February 2019) - Galleas, W
Abstract: In this work we elaborate on a previous result relating the partition function of the six-vertex model with domain-wall boundary conditions to eigenvalues of a transfer matrix. More precisely, we express the aforementioned partition function as a determinant of a matrix with entries that are eigenvalues of the transfer matrix of the anti-periodic six-vertex model.